Bílkoviny výlisků olejnin, jejich izolace a možnosti uplatnění - Bárta, Jan; Bártová, Veronika; Jarošová, Markéta; Švajner, Josef (Chemické listy, 2021)
Oilseed cakes and meals are obtained as by-products after oil extraction. They contain 15–60 % proteins with a relatively good amino acid proportion and other valuable components such as dietary fibre, residual fat, polyphenols etc. Proteins are above all represented by globulins, especially 11-12S globulin, and albumins. Oilseed cakes are often used as feed for farm animals but they can be valorised in the form of flour and protein concentrate or by an isolation using dry or wet processes. In this work, a characterization of seed proteins of selected oilseed crops and methods of protein isolation are presented. Possibilities of oilseed protein products use in human nutrition and food products are evaluated.